Dominant variants in the splicing factor PUF60 cause a recognizable syndrome with intellectual disability, heart defects and short stature - El Chehadeh, Salima; Kerstjens-Frederikse, Wilhelmina S; Thevenon, Julien; Kuentz, Paul; Bruel, Ange-Line; Thauvin-Robinet, Christel; Bensignor, Candace; Dollfus, Hélène; Laugel, Vincent; Rivière, Jean-Baptiste; Duffourd, Yannis; Bonnet, Caroline; et al. (European journal of human genetics, 2016)
Verheij syndrome, also called 8q24.3 microdeletion syndrome, is a rare condition characterized by ante- and postnatal growth retardation, microcephaly, vertebral anomalies, joint laxity/dislocation, developmental delay (DD), cardiac and renal defects and dysmorphic features. Recently, PUF60 (Poly-U Binding Splicing Factor 60 kDa), which encodes a component of the spliceosome, has been discussed as the best candidate gene for the Verheij syndrome phenotype, regarding the cardiac and short stature phenotype. To date, only one patient has been reported with a de novo variant in PUF60 that probably affects function (c.505C>T leading to p.(His169Tyr)) associated with DD, microcephaly, craniofacial and cardiac defects. Additional patients were required to confirm the pathogenesis of this association and further delineate the clinical spectrum. Here we report five patients with de novo heterozygous variants in PUF60 identified using whole exome sequencing. Variants included a splice-site variant (c.24+1G>C), a frameshift variant (p.(Ile136Thrfs*31)), two nonsense variants (p.(Arg448*) and p.(Lys301*)) and a missense change (p.(Val483Ala)). All six patients with a PUF60 variant (the five patients of the present study and the unique reported patient) have the same core facial gestalt as 8q24.3 microdeletions patients, associated with DD. Other findings include feeding difficulties (3/6), cardiac defects (5/6), short stature (5/6), joint laxity and/or dislocation (5/6), vertebral anomalies (3/6), bilateral microphthalmia and irido-retinal coloboma (1/6), bilateral optic nerve hypoplasia (2/6), renal anomalies (2/6) and branchial arch defects (2/6). These results confirm that PUF60 is a major driver for the developmental, craniofacial, skeletal and cardiac phenotypes associated with the 8q24.3 microdeletion.
Keywords: chromozomální delece; Female; Phenotype; Repressor Proteins; dítě; předškolní dítě; sestřih RNA; Heart Defects, Congenital; RNA Splicing; represorové proteiny; ženské pohlaví; Exome; High-Throughput Nucleotide Sequencing; lidské chromozomy, pár 8; Adolescent; RNA Splicing Factors; lidé; posunová mutace; exom; sestřihové faktory; Frameshift Mutation; Intellectual Disability; Male; Chromosome Deletion; vysoce účinné nukleotidové sekvenování; Child, Preschool; nanismus; Dwarfism; Chromosomes, Human, Pair 8; Child; vrozené srdeční vady; mužské pohlaví; fenotyp; mentální retardace; mladiství; Humans